The Hilltop Pre-HE Model™: Hospice Eligibility and Advanced Care Planning Fact Sheet - The Hilltop Institute (The Hilltop Institute, 2024)
The Hilltop Pre-HE Model™—which generates the rankings for the Hospice Eligibility and Advanced Care Planning (Pre-HE) scores—is designed to support proactive advanced care planning discussions by estimating a patient’s risk of eligibility for hospice. The Pre-HE Model provides risk scores and reasons for risk for all attributed beneficiaries of Maryland Primary Care Program (MDPCP) practices every month in order to identify patients that are potentially appropriate for hospice care and to provide care teams with information that can guide the sensitive and difficult conversations about end-of-life care with patients and their families.